Exploring the Capabilities of Drones for Undergraduate Research - Wheeler, Erlan E. (Proceedings of the Wisconsin Space Conference, 2016)
Carthage College initiated a program to explore the use of drones in undergraduate research at a small, liberal-arts college. We provided an environment of â€œtoysâ€ for the students to explore and encouraged them to choose their own projects. Our experience was that projects involving mapping, 3D modeling, and programming were more successful than engineering-oriented projects, but this could be due to the expertise of the faculty facilitator. Overall, the experience was highly rewarding and educational to all involved.Â